The association between controlling nutritional status and postoperative pulmonary complications in patients with colorectal cancer - Li, Yafang; Nie, Chuang; Li, Na; Liang, Jieying; Su, Ning; Yang, Chunhua (Frontiers in Nutrition, 2025)
BackgroundPostoperative pulmonary complications (PPCs) significantly impact surgical outcomes, and Controlling Nutritional Status (CONUT) score, a simple and easily available nutritional score, has been demonstrated to be significantly associated with postoperative patient outcomes and complications, including PPCs. However, there are few studies that specifically focus on patients undergoing radical surgery for colorectal cancer (CRC).MethodsWe retrospectively analyzed the clinical data of 2,553 patients who underwent radical surgery for CRC at the Sixth Affiliated Hospital of Sun Yat-sen University. Patients were divided into three groups: normal nutrition group (CONUT≤1), mild malnutrition group (2 ≤ CONUT≤4), and moderate-to-severe malnutrition group (CONUT≥5). Risk factors for PPCs and all-cause mortality were evaluated by multivariate regression. In addition, we assessed surgical outcomes including ICU admission, hospital stay, 1-year mortality and tumor-related mortality.ResultsThe incidence of PPCs was 9.0% (n = 230). Multiple regression showed that the higher the CONUT score, the higher the risk of PPCs (mild malnutrition group vs. normal nutrition group, OR: 1.61, 95% CI: 1.18–2.20, p = 0.003; moderate-to-severe malnutrition group vs. normal nutrition group, OR: 2.41, 95% CI: 1.51–3.84, p < 0.001). All-cause mortality was significantly higher in moderate-to-severe malnutrition group than that in normal nutrition group, HR: 1.88, (95% CI: 1.34–2.62, p < 0.001). Older age, male sex, chronic heart disease, open surgery, blood transfusion during surgery, distant metastasis of tumor and colon tumor were all risk factors for PPCs. Furthermore, the malnutrition groups had poor surgical outcomes including postoperative pneumonia (mild vs. normal nutrition, OR: 1.64, 95% CI: 1.07–2.52, p = 0.024; moderate-to-severe vs. normal nutrition, OR: 2.51, 95% CI: 1.36–4.62, p = 0.00), ICU admission (mild vs. normal nutrition, OR: 2.16, 95% CI: 1.31–3.56, p = 0.002; moderate-to-severe vs. normal nutrition, OR: 3.86, 95% CI: 2.07–7.20, p < 0.001), hospital stay ≥14 days (mild vs. normal nutrition, OR: 1.30, 95% CI: 1.08–1.56, p = 0.006) and 1-year mortality (mild vs. normal nutrition, HR: 1.65, 95% CI: 1.11–2.46, p = 0.014; moderate-to-severe vs. normal nutrition, HR: 2.27, 95% CI: 1.28–4.02, p = 0.005).ConclusionThe preoperative CONUT score is a potential indicator for predicting PPCs and surgical outcomes in CRC patients.